2019
DOI: 10.1073/pnas.1812951116
|View full text |Cite
|
Sign up to set email alerts
|

Soluble matrix protein is a potent modulator of mesenchymal stem cell performance

Abstract: We challenge the conventional designation of structural matrix proteins primarily as supporting scaffolds for resident cells. The extracellular matrix protein tropoelastin is classically regarded as a structural component that confers mechanical strength and resilience to tissues subject to repetitive elastic deformation. Here we describe how tropoelastin inherently induces a range of biological responses, even in cells not typically associated with elastic tissues and in a manner unexpected of typical substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 68 publications
(96 reference statements)
2
58
0
Order By: Relevance
“…ECM regulation of cell behavior, such as migration, adhesion, and differentiation are likely contributing factors in various biochemical and physical signaling phenomena, such as mechanotransduction and topographic influences 58‐61 . A recent study demonstrated an important role of soluble matrix protein, that is, tropoelastin, as an important regulator of MSC performance, such as proliferation and phenotypic maintenance 62 . This is in agreement with our study showing that soluble fraction of tendon ECM enhanced ASC proliferation and tenogenic committment.…”
Section: Discussionsupporting
confidence: 92%
“…ECM regulation of cell behavior, such as migration, adhesion, and differentiation are likely contributing factors in various biochemical and physical signaling phenomena, such as mechanotransduction and topographic influences 58‐61 . A recent study demonstrated an important role of soluble matrix protein, that is, tropoelastin, as an important regulator of MSC performance, such as proliferation and phenotypic maintenance 62 . This is in agreement with our study showing that soluble fraction of tendon ECM enhanced ASC proliferation and tenogenic committment.…”
Section: Discussionsupporting
confidence: 92%
“…45,46 This is worthwhile because tropoelastin-integrin crosstalk activates the mechanosensing pathways that result in enhanced cell focal adhesion and cytoskeleton organization. 26 Still, these differences in AR were no longer observed after 14 days ( Figure 4B). While the AR of cells on TROPO remained unchanged from day 5 to 14, it significantly increased on uncoated and PDA-coated samples.…”
mentioning
confidence: 85%
“…7,[18][19][20] In a tissue engineering perspective, TROPO has been incorporated as a bulk material to build highly elastic hydrogels, 21,22 films produced through casting 23 or electrospun fibrous scaffolds 24,25 to enhance cell adhesion, proliferation and migration, neo-vascularization and even direct stem cell commitment. 26 TROPO has also been covalently bounded to plasma activated surfaces to enhance cell attachment and potentiate integration within the body. 27,28 Based on the potential role of elastin over native tenocytes, here we propose a novel biomimetic strategy that combines the advantages of 3D nano-to-macro hierarchical and anisotropic scaffolds with the biological potential of TROPO.…”
Section: Introductionmentioning
confidence: 99%
“…Which MMPs are involved is not entirely understood, but MMP‐1 has been found to have a role in tissue invasion by MSCs 114 . Matrix components such as tropoelastin have also been found to increase homing and proliferation of MSCs in development and in wound repair 115 . Last, as in HSPC homing, the MSCs must migrate to the site of injury guided by chemotactic signals such as PDGFα, 116 insulin growth factor‐1, 117 CXCL12, and other chemokines.…”
Section: Msc Homingmentioning
confidence: 99%